2013
DOI: 10.14742/ajet.317
|View full text |Cite
|
Sign up to set email alerts
|

So the kids are busy, what now? Teacher perceptions of the use of hand-held game consoles in West Australian primary classrooms

Abstract: Games technology in the form of hand-held game consoles (HGCs) when focussed on specific academic skill development has the capacity to engage students in learning and in turn produce positive academic results. This current research explores teacher perceptions of the implementation of HGCs to enhance the development of mental maths skills (namely the recall of single digit addition, subtraction and multiplication sums) in nine Year 4 classrooms and, through a series of structured interviews and observations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As with much change, some classroom practitioners understandably lament for lessons past, or as Tapscott (2009, p. 128) points out in his exploration of learning in schools for students of the 'net-generation'; "old paradigms die hard". A report on digital games in the classroom found that teachers who played digital games for pleasure were much more likely to use digital games in their classrooms than those who did not (Takeuchi & Vaala, 2014); therefore, it is not surprising that some classroom teachers have expressed a need for guidance on how to use DGBL effectively (Greenhow, Robelia, & Hughes, 2009;Jukes, McCain, & Crockett, 2010;O'Rourke, Main, & Ellis 2013).…”
Section: Literature Review Digital Games Based Learning (Dgbl) In Thementioning
confidence: 99%
See 4 more Smart Citations
“…As with much change, some classroom practitioners understandably lament for lessons past, or as Tapscott (2009, p. 128) points out in his exploration of learning in schools for students of the 'net-generation'; "old paradigms die hard". A report on digital games in the classroom found that teachers who played digital games for pleasure were much more likely to use digital games in their classrooms than those who did not (Takeuchi & Vaala, 2014); therefore, it is not surprising that some classroom teachers have expressed a need for guidance on how to use DGBL effectively (Greenhow, Robelia, & Hughes, 2009;Jukes, McCain, & Crockett, 2010;O'Rourke, Main, & Ellis 2013).…”
Section: Literature Review Digital Games Based Learning (Dgbl) In Thementioning
confidence: 99%
“…These observations suggest that the teachers in the comparison classrooms were selecting strategies intended to engage students in mental-maths activities. Observation of a variety of teacher practice in the intervention classrooms (described by O'Rourke, Main, & Ellis, 2013) as 'the guiding teacher', 'the facilitating teacher' and the 'interactive teacher'), illustrated that regardless of the different teaching approaches when using the HGCs, these classroom pedagogies appeared to have little influence on the positive student perceptions and improvements in mental-maths skills. It was evident in classroom observations that by maintaining set classroom structures the HGCs had the capacity to engage and motivate students, irrespective of the approach of the teacher (O'Rourke et al, 2013).…”
Section: Teacher Practicementioning
confidence: 99%
See 3 more Smart Citations